Individual contributions to group behaviour in the cooperatively breeding southern ground-hornbill Bucorvus leadbeateri - Middleton, Kyle-Mark (Department of Biological Sciences, 2023)
Cooperative breeding, in which individuals other than breeders contribute to raising offspring, has been the focus of much scientific research over the past decades. Why do some individuals help to raise offspring that are not their own? In birds, cooperative breeding is found mainly in harsh regions with greater environmental variability, such that individuals might do better to help relatives than attempt to breed themselves. However, in some bird families cooperative breeding is instead associated with stable and benign environments, suggesting that species may form cooperative groups for different reasons. Most studies have focused on the benefits that additional group members bring to offspring, by increasing provisioning rates, nestling survival, and overall reproductive output. These benefits have been suggested to mitigate the effects of harsh climatic conditions and to be particularly important in the face of anthropogenic climate change, during which increases in temperature extremes and interannual rainfall variability are expected to push species' tolerance to the limit. However, other advantages of group living have been less often considered; for example, collective territory defence is common in cooperative breeders and ensures exclusive access to crucial resources such as food, nesting sites, and mates. A better understanding of the diverse factors favouring cooperative behaviour can offer insights as to why, and in what environmental conditions, social behaviour has evolved, and whether and how it might help animal populations to cope with environmental change. Therefore, the aims of this thesis were to investigate how individuals within cooperative groups contribute to reproduction and territory defence in an atypical cooperative breeder, the southern ground-hornbill Bucorvus leadbeateri. The large body size and exceptionally long lifespan of ground-hornbills leads to a “slow” life-history strategy, providing a striking contrast to most wellstudied avian cooperative breeders, which tend to be small, relatively short-lived passerines. Furthermore, while the hornbill family is usually associated with mesic, stable environments, groundhornbills inhabit semi-arid, fluctuating environments. Studying them thus may shed light on why cooperative breeding might be favoured in both harsh, fluctuating environments, as well as benign, stable environments. I use a combination of my own data collected over five years (2017‒2022) and long-term data collected from the APNR Southern Ground-Hornbill Project (2000‒2022) to test the effects of environmental and social factors (climatic conditions, group size and composition, and age structure of group members) on reproductive and territorial cooperative behaviour. The first two data chapters focus on how group members influence provisioning efforts and reproductive outcomes, and whether group members of different ages can mitigate the effects of harsh climatic conditions. My results showed that high temperatures and low rainfall had generally negative effects on reproduction, and that cooperative breeding provided some reproductive benefits, but did not act as a buffer to provisioning rates or reproductive outputs. Specifically, we showed that adult males had the highest provisioning rates and provisioned larger items, but the additive care they provided did not buffer the effects of high temperatures. Additionally, we showed that hot and dry conditions were associated with decreased breeding probability, later laying dates, and decreased nestling body mass, and that group composition did not significantly mitigate these negative effects. Instead, our results suggested that group or territory quality may be a more important factor in determining reproductive success. The second two data chapters focus on territory defence. Specifically, I asked how different group members contributed to the species' characteristic deep booming chorus vocalisations used to advertise territories, and how responses to territorial intrusions were mediated by caller identity and group size. I showed that calls were significantly different between the sexes, and that females produced sequences of calls that formed unique melodies that could be automatically assigned to the correct individual with a 94% success rate. Melodies are an effective way of signalling individual identity in long distance communication, as this acoustic information travels well when composed of low-pitched sounds. Therefore, since each group generally contains only one adult female, groups can be identified by the female's signature. Next, I showed that there were no clear effects of intruder group identity on the responses of territory holders, but found that group size was positively associated with aggressive responses, indicating that group living may provide resource defence benefits. Overall, the findings in this thesis indicated that group living provided benefits for territory defence and to a lesser extent, reproduction, and that individual contributions of different group members varied between different cooperative behaviours. Despite ground-hornbills inhabiting semiarid regions with harsh climatic conditions, the presence of additional group members of different ages during reproduction were insufficient to mitigate the negative effects of high temperature and low rainfall. However, the likely benefits provided by additional helpers to territory defence suggest that the ecology, longevity, and slow-development of ground-hornbills may render the presence of additional helpers less critical for reproduction, but more important for resource defence. Further research into other group behaviours such as predator vigilance, foraging and hunting, and energy conservation would provide additional insights into other benefits that cooperative breeding might provide. This study implies that a species' life-history strategy may be an important mechanism determining the benefits individuals receive from breeding cooperatively, and so help to explain the ecological correlates and diversity of forms taken by cooperative breeding, including the remarkable biology of the southern ground-hornbill.